Retrospective motion correction for cardiac multi‐parametric mapping with dictionary matching‐based image synthesis and a low‐rank constraint - Chen, Haiyang; Emu, Yixin; Gao, Juan; Chen, Zhuo; Aburas, Ahmed; Hu, Chenxi (Magnetic resonance in medicine, 2025)
Purpose To develop a model‐based motion correction (MoCo) method that does not need an analytical signal model to improve the quality of cardiac multi‐parametric mapping. Methods The proposed method constructs a hybrid loss that includes a dictionary‐matching loss and a signal low‐rankness loss, where the former registers the multi‐contrast original images to a set of motion‐free synthetic images and the latter forces the deformed images to be spatiotemporally coherent. We compared the proposed method with non‐MoCo, a pairwise registration method (Pairwise‐MI), and a groupwise registration method (pTVreg) via a free‐breathing Multimapping dataset of 15 healthy subjects, both quantitatively and qualitatively. Results The proposed method achieved the lowest contour tracking errors (epicardium: 2.00 ± 0.39 mm vs 4.93 ± 2.29 mm, 3.50 ± 1.26 mm, and 2.61 ± 1.00 mm, and endocardium: 1.84 ± 0.34 mm vs 4.93 ± 2.40 mm, 3.43 ± 1.27 mm, and 2.55 ± 1.09 mm for the proposed method, non‐MoCo, Pairwise‐MI, and pTVreg, respectively; all p < 0.01) and the lowest dictionary matching errors among all methods. The proposed method also achieved the highest scores on the visual quality of mapping (T1: 4.74 ± 0.33 vs 2.91 ± 0.82, 3.58 ± 0.87, and 3.97 ± 1.05, and T2: 4.48 ± 0.56 vs 2.59 ± 0.81, 3.56 ± 0.93, and 4.14 ± 0.80 for the proposed method, non‐MoCo, Pairwise‐MI, and pTVreg, respectively; all p < 0.01). Finally, the proposed method had similar T1 and T2 mean values and SDs relative to the breath‐hold reference in nearly all myocardial segments, whereas all other methods led to significantly different T1 and T2 measures and increases of SDs in multiple segments. Conclusion The proposed method significantly improves the motion correction accuracy and mapping quality compared with non‐MoCo and alternative image‐based methods.